A low carbon balance triggers Microvine inflorescence abscission at high temperatures - Luchaire, Nathalie; Torregrosa, Laurent Jean-Marie; Gibon, Yves; Rienth, Markus; Romieu, Charles; Ageorges, Agnès; Turc, Olivier; Muller, Bertrand; Pellegrino, Anne (Frontiers in Horticulture, 2023)
Introduction Global warming is a major threat to yield sustainability in most crops, including grapevine. Whether or not grapevine fruitfulness is impaired by an imbalance between carbon supply and demand caused by high temperatures was investigated in the present study. Methods Five experiments were conducted on Microvine, a natural mutant of grapevine that is insensitive to gibberellins, presents with a dwarf stature, and has continuous flowering along the vegetative axes. The last property was used to infer temporal patterns of inflorescence development from their spatial distribution at harvest. Two sets of plants, characterized by low or high levels of initial shoot vigor, were grown under contrasting day and night temperatures: 22°C/12°C and 30°C/20°C. Results and discussion The rate of leaf development of the main shoot was stable, regardless of the initial vigor and temperature treatment. In contrast, the warm temperatures delayed the timing of flowering for low-vigor plants or the onset of ripening for high-vigor plants. Fruitfulness was impaired by high temperatures as a result of the abscission of young inflorescences (before the flowering stage). From a careful spatiotemporal analysis of cluster abscission, we concluded that inflorescence drop under elevated temperatures was triggered by the increase in plant carbon demand due to the oldest clusters starting to unload sugars. Elevated temperatures may have also lowered the carbohydrate supply in the zone of inflorescence abscission due to the higher leaf respiration while all organ growth demand was maintained. Interestingly, inflorescence abscission occurred earlier when whole-plant vigor was low and was followed by a recovery period, in spite of a lower non-structural sugar status than in high-vigor plants. Taken together, our results suggest that inflorescence abscission is linked to the variations of the carbon pool induced by changes in temperature and not to its absolute value. Our study, therefore, provides new hypotheses about the impacts of warm temperatures on the regulation of temperature-induced reproductive failure in grapevine.